(untitled) (Progressive Agriculture, 2013)
To increase production and import substitution of spices, the Ministry of Agriculture has launched the Action Plan by facilitating supply of improved seed, fertilizer along with training for the farmers through institutional linkages of the all-public research and extension agencies from 2002 to 2006. The study was undertaken to evaluate the impact of the Action Plan and to identify the current status of spice crops in relation to production, area, yield, consumption and marketing system in the selected area of spice crops in Bangladesh. An intensive survey of beneficiaries of the five major spices namely onion, garlic, ginger, chili and turmeric from the four region of Bangladesh under Action Plan was done to have necessary information during January to June 2006. Among five major spices, area production, import, demand and net availability of onion occupied higher position compared to others. From the benchmark period (2001-2002) area, production and yield of onion increased from 37 thousand hectare, 150 thousand metric ton and 4 ton/hectare to 141 thousand hectare, 754 thousand metric ton and 5.35 ton/hectare respectively. As a consequence net availability and per capita consumption increased. Area, production, yield, per capita availability and net availability of garlic, ginger, chili and turmeric also increased from the benchmark period to 2005. It was observed that The Action Plan has been successfully generated positive impact on cropping system and socio-economic condition. Estimation of financial profitability shown that ginger appeared to be highly profitable spice crops having net return Tk. 2,82,011 per hectare followed by chili (Tk. 71,441 per hectare), turmeric (Tk. 65,423 per hectare), garlic (Tk. 50,281 per hectare) and onion (Tk. 38,281 per hectare) accordingly. DOI: http://dx.doi.org/10.3329/pa.v19i2.16965 Progress. Agric. 19(2): 229 - 241, 2008